2017
DOI: 10.1002/hyp.11113
|View full text |Cite
|
Sign up to set email alerts
|

Generation of continuous surface soil moisture dataset using combined optical and thermal infrared images

Abstract: Surface soil moisture (SSM) is a critical variable for understanding water and energy flux between the atmosphere and the Earth's surface. An easy to apply algorithm for deriving SSM time series that primarily uses temporal parameters derived from simulated and in situ datasets has recently been reported. This algorithm must be assessed for different biophysical and atmospheric conditions by using actual geostationary satellite images. In this study, two currently available coarse‐scale SSM datasets (microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Due to the advantage of remote sensing observations, many efforts have been dedicated to determining the surface soil moisture for regional or even global applications [9][10][11][12][13][14]. Early field experiments demonstrated that passive microwave emissions and active microwave scatter are a function of the dielectric constant of the surface soil layer, and that the dielectric constant is related to the soil water content.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantage of remote sensing observations, many efforts have been dedicated to determining the surface soil moisture for regional or even global applications [9][10][11][12][13][14]. Early field experiments demonstrated that passive microwave emissions and active microwave scatter are a function of the dielectric constant of the surface soil layer, and that the dielectric constant is related to the soil water content.…”
Section: Introductionmentioning
confidence: 99%
“…Interferometric synthetic aperture radar (InSAR) and light detection and ranging (LiDAR) data can be used to monitor structural changes in and displacement of a tailings dam before failure [29,53,54]. Optical and thermal satellite data can be used to monitor environmental impacts such as water and soil pollution near tailings dams [55,56]. Based on multi-resource remote sensing data, monitoring systems and platforms can help reduce the probability of failures effectively and also mitigate the consequences.…”
Section: Tailings Dams In the Jing-jin-ji Regionmentioning
confidence: 99%
“…The increasing number of geostationary satellites is facilitating the development of more practical SSM retrieval methods with higher spatial and temporal resolutions [31]- [36]. Geostationary satellites have a higher frequency of observations than do polar orbiting satellites and can produce 48 to 96 images per day with a fixed observation angle for a given pixel, substantially enriching our understanding of terrestrial water and energy budgets.…”
Section: Introductionmentioning
confidence: 99%